Laser‐Triggered Vapor‐Phase Anion Exchange on All‐Inorganic Perovskites for Multicolor Patterns and Microfabrications. Issue 4 (9th December 2022) - Sheng, Yuhang; Zha, Yanfang; Feng, Xuying; Xing, Fangjian; Di, Yunsong; Liu, Cihui; Zhang, Xiaowei; Gan, Zhixing
Abstract: Anion exchange reaction is a facile postsynthesis approach to modulate the bandgaps of perovskites to meet the demands in full visible spectrum. However, conventional anion exchanges are usually conducted in solutions, limiting their applications in fabricating high‐quality blue‐emitting perovskites and multicolor fluorescent patterns. Herein, a laser‐triggered vapor‐phase anion exchange (LTVAE) method is developed to convert CsPbBr3 perovskites with different morphologies (nanocrystal films/solution, microcrystals, and microplatelets) into CsPb(Br x Cl1‐ x )3 and CsPb(Br x I1‐ x )3 perovskites. Thus, the green fluorescence is converted into blue and red fluorescence. Moreover, the deep‐blue fluorescence obtained by LTVAE shows a high quantum yield (QY) of 67.2%. Based on the mask‐assistant LTVAE, multicolor fluorescent patterns are fabricated, which are very significant for anticounterfeit and multicolor displays. Furthermore, a polymer‐assistant LTVAE method is developed to improve the stability of the multicolor fluorescent patterns. More importantly, micro‐heterojunctions with two different fluorescent colors are successfully constructed on a single CsPbBr3 microplatelet, which paves the way for microfabrications. Abstract : A laser‐triggered vapor‐phase anion exchange (LTVAE) method is developed for the fabrication of multicolor fluorescent patterns on perovskites, which is controllable, convenient, and compatible with conventional semiconductor process. The LTVAE is applicable for CsPbBr3 perovskites with different morphologies. Based on the mask/polymer‐assistant LTVAE methods, multicolor fluorescent patterns and micro‐heterojunctions are fabricated.